Prevalence of hypospadias and other genital anomalies among singleton births, 1988–1997, in Scotland. Issue 2 (1st March 2004) - Ahmed, S F; Dobbie, R; Finlayson, A R; Gilbert, J; Youngson, G; Chalmers, J; Stone, D
Abstract : Background: Considerable debate exists on the epidemiology of genital anomalies. Methods: All genital anomalies, excluding undescended testes, were identified from neonatal returns, stillbirth and infant death survey records, and returns relating to hospital admissions and linked to form infant profiles on a cohort of singleton births between 1988 and 1997 with follow up for a minimum of three years. Findings: The mean genital anomaly prevalence rate in Scotland was calculated at 4.6 per 1000 births varying from 4.0 per 1000 births in 1988 to 5.9 per 1000 births in 1996. However, there was no evidence of a clear trend to an increasing prevalence of hypospadias, which constituted 73% of the anomalies studied. Logistic regression analysis of the data also showed this rate to be independently associated with being relatively small for gestational age (odds ratio (OR) 1.43, p < 0.001) and increasing maternal age (OR 1.2, p < 0.05). Infants born in deprived areas, as judged by the Carstairs deprivation score, were least likely to have a genital anomaly (OR 0.73, p < 0.01). Interpretation: A new linked register of congenital genital anomalies in Scotland suggests that over a decade, the birth prevalence of genital anomalies has changed little. The associations between genital anomalies, maternal age, and socioeconomic deprivation require further study.